Offense and Defense in Granulomatous Inflammation Disease - Wang, Xinwen; Liu, Yuan (Frontiers in Cellular and Infection Microbiology, 2022)
Granulomatous inflammation (GI) diseases are a group of chronic inflammation disorders characterized by focal collections of multinucleated giant cells, epithelioid cells and macrophages, with or without necrosis. GI diseases are closely related to microbes, especially virulent intracellular bacterial infections are important factors in the progression of these diseases. They employ a range of strategies to survive the stresses imposed upon them and persist in host cells, becoming the initiator of the fighting. Defense capacity of hosts is another influence factor, which is thought to combine to determine the result of the fighting. With the development of gene research technology, many human genetic loci were identified to be involved in GI diseases susceptibility, providing more insights into and knowledge about GI diseases. The current review aims to provide an update on the most recent progress in the identification and characterization of bacteria in GI diseases in a variety of organ systems and clinical conditions, and examine the invasion and escape mechanisms of pathogens that have been demonstrated in previous studies, we also review the existing data on the predictive factors of the host, mainly on genetic findings. These strategies may improve our understanding of the mechanisms underlying GI diseases, and open new avenues for the study of the associated conditions in the future.